2014
DOI: 10.1007/s12155-014-9530-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot-Pressing Temperature on the Subsequent Enzymatic Saccharification and Fermentation Performance of SPORL Pretreated Forest Biomass

Abstract: Methods to increase the energy density of biofuel feedstock for shipment are important towards improving supply chain efficiency in upstream processes. Towards this end, densified pretreated lignocellulosic biomass was produced using hot-pressing. The effects of fiber hornification induced by hot-pressing on enzymatic digestibilities of lodgepole pine and poplar NE222 wood chips pretreated by sulfite pretreatment to overcome recalcitrance of lignocelluloses (SPORL) were examined. Pretreated wood chips were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The enzyme preparation purchased in the off-site case was based on existing data for the commercially available cellulase cocktail Cellic CTec3 from Novozymes A/S. Assuming 213 FPU mL −1 for the cocktail [ 46 , 47 ] and a density of 1.1 g mL −1 (valid for CTec2, the predecessor product) [ 48 ], enzyme dosage was calculated to be 30.4 g enzyme cocktail kg −1 DM (dry matter) wood. This dosage is used for the base case scenario, but as it is a crucial factor for the resulting costs and GHG emissions, alternative assumptions were tested in sensitivity analyses (see “ Alternative enzyme data for sensitivity analyses ” section).…”
Section: Methodsmentioning
confidence: 99%
“…The enzyme preparation purchased in the off-site case was based on existing data for the commercially available cellulase cocktail Cellic CTec3 from Novozymes A/S. Assuming 213 FPU mL −1 for the cocktail [ 46 , 47 ] and a density of 1.1 g mL −1 (valid for CTec2, the predecessor product) [ 48 ], enzyme dosage was calculated to be 30.4 g enzyme cocktail kg −1 DM (dry matter) wood. This dosage is used for the base case scenario, but as it is a crucial factor for the resulting costs and GHG emissions, alternative assumptions were tested in sensitivity analyses (see “ Alternative enzyme data for sensitivity analyses ” section).…”
Section: Methodsmentioning
confidence: 99%
“…With an increase of preheating temperature and time, a decreasing trend of WRV of briquettes was observed. Zhang et al performed a study using a hot press to compress biomass and reported fiber hornification resulted in reduction of substrate water swelling abilities and the degree of hornification increased with the increase of pressing temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Briquetting with preheating for 10 min at 75 and 125°C showed negative effects on sugar yields, meaning that excessive preheating before briquetting is detrimental. Bals et al and Zhang et al suggested that heat during densification may introduce hornification that caused a negative effect on sugar conversion. Preheating for 10 min at 75 and 125°C before briquetting may have resulted in irreversible structural modifications, which hindered the interaction between biomass and water during pretreatment, and therefore decreased the accessibility of the cellulose to enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Moreover, lignin softens and induces cohesiveness that aids in biomass pellet production when the temperature during densification reaches the glass transition temperature of lignin. 19 On the negative side, the mechanical compression during densification induces microstructural shrinkage and a reduction in the porosity of feedstock; 20 the softened lignin migrates and relocates to the surface of biomass, both of which prevent enzymes from contacting cellulose. 21 Various parameters, including pressure, temperature, and biomass moisture, play different roles in densification and thereby affect enzymatic digestibility.…”
Section: Introductionmentioning
confidence: 99%